Nanometrology, Standardization and Regulation of Nanomaterials in Brazil: a Proposal for an Analytical-Prospective Model - Giménez Ledesma,Ana Rusmerg (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2013)
The main objective of this paper is to propose an analytical-prospective model as a tool to support decision-making processes concerning metrology, standardization and regulation of nanomaterials in Brazil, based on international references and ongoing initiatives in the world. In the context of nanotechnology development in Brazil, the motivation for carrying out this research was to identify potential benefits of metrology, standardization and regulation of nanomaterials production, from the perspective of future adoption of the model by the main stakeholders of development of these areas in Brazil. The main results can be summarized as follows: (i) an overview of international studies on metrology, standardization and regulation of nanomaterials, and nanoparticles, in special; (ii) the analytical-prospective model; and (iii) the survey questionnaire and the roadmapping tool for metrology, standardization and regulation of nanomaterials in Brazil, based on international references and ongoing initiatives in the world.